Stable Nano‐Encapsulation of Lithium Through Seed‐Free Selective Deposition for High‐Performance Li Battery Anodes. Issue 7 (10th January 2020) - Ye, Weibin; Pei, Fei; Lan, Xiangna; Cheng, Yong; Fang, Xiaoliang; Zhang, Qiaobao; Zheng, Nanfeng; Peng, Dong‐Liang; Wang, Ming‐Sheng
Abstract: Metallic lithium has long been deemed as the ultimate anode material for future high‐energy‐density Li batteries. However, the commercialization of Li metal anodes remains hindered by some major hurdles including their huge volume fluctuation during cycling, unstable solid electrolyte interface (SEI), and dendritic deposition. Herein, the concept of nano‐encapsulating electrode materials is attempted to tackle these problems. Nitrogen‐doped hollow porous carbon spheres (N‐HPCSs), prepared via a facile and low‐cost method, serve as the nanocapsules. Each N‐HPCS has a lithophilic carbon shell with a thin N‐rich denser layer on its inner surface, which enables preferential nucleation of Li inside the hollow sphere. It is demonstrated by in situ electron microscopy that these N‐HPCS hosts allow Li to be encapsulated in a highly reversible and repeatable manner. Ultralong Li filling/stripping cycling inside single N‐HPCSs is achieved, up to 50 cycles for the first time. Li ion transport across multiple connected N‐HPCSs, leading to long‐range Li deposition inside their cavities, is visualized. In comparison, other types of carbon spheres with modified shell structures fail in encapsulating Li and dendrite suppression. The necessity of the specific shell design is therefore confirmed for stable Li encapsulation, which is essential for the N‐HPCS‐based anodes to achieve superior cycling performance. Abstract : Specifically designed carbon nanospheres featured with a thin N‐rich dense layer on their inner surface enable preferential nucleation of Li inside their hollow cavities. As revealed by in situ transmission electron microscopy observation and electrochemical testing, these nanosphere hosts allow Li to be encapsulated in a highly reversible and repeatable manner, leading to high Coulombic efficiency and good cycling stability.